2011
DOI: 10.1097/bot.0b013e3181f8d9c3
|View full text |Cite
|
Sign up to set email alerts
|

Adult Proximal Humerus Locking Plate for the Treatment of a Pediatric Subtrochanteric Femoral Nonunion: A Case Report

Abstract: Nonunions of pediatric subtrochanteric femur fractures are exceedingly rare and have to date not been reported in the literature. We present the case of an 11-year-old boy who developed such a nonunion after open reduction internal fixation using a pediatric locked proximal femur plate. Using an adult proximal humerus locking plate, adequate proximal fixation of the nonunion was obtained. Furthermore, previously placed distal screw holes were safely bridged and the biomechanical environment around the nonunion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Fernandez et al 5 treated six cases of non-union of forearm shaft fractures in children after intramedullary nailing. Behr et al 6 reported seven cases of scaphoid, Cortes et al 7 treated one case of non-union following subtrochanteric femoral fracture in a child. Pourtaheri8 reported one case of clavicle non-union.…”
Section: Discussionmentioning
confidence: 99%
“…Fernandez et al 5 treated six cases of non-union of forearm shaft fractures in children after intramedullary nailing. Behr et al 6 reported seven cases of scaphoid, Cortes et al 7 treated one case of non-union following subtrochanteric femoral fracture in a child. Pourtaheri8 reported one case of clavicle non-union.…”
Section: Discussionmentioning
confidence: 99%
“…The locking screws and plate offer stable mechanical support to the bone, and reduce potential damage to surrounding blood supply. [ 15 , 16 ] The rational length of the plate avoids damage to epiphyseal cartilage, which is especially beneficial in our case.…”
Section: Discussionmentioning
confidence: 90%
“…DBX has been described in a case report, showing the successful treatment of a subtrochanteric nonunion of an 11-year-old patient with an adult proximal humeral locking plate and additional grafting with DBX. 32 This study provides level IV evidence that DBX may be used as a bone graft substitute to treat nonunion.…”
Section: Resultsmentioning
confidence: 85%
“…For example, the use of DBX is only described in a small case series of sternum fractures 30 and a single case report of nonunion. 32 Furthermore, the case-control study that used Grafton DBM or OrthoBlast in fracture treatment 48 included only 13 and 15 cases and did not have a control group. The RCT by Hierholzer et al 53 which concludes that grafting humeral nonunions with Grafton DBM is as effective as using autologous bone reported union rates of 97% and 100%, respectively, after four months.…”
Section: Discussionmentioning
confidence: 99%